USER PERCEPTION OF MOBILE COMMUNITY ACCESS POINT (MCAP) SERVICES IN KULON PROGO DISTRICT, DIY PROVINCE BASED ON TECHNOLOGY ACCEPTANCE MODEL (TAM) - Nina Amini; Yolanda Presiana Desi (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2019)
Mobile Community Access Point (MCAP) service is one of the programs to fulfill the Universal Service Obligation to encourage the acceleration of internet access for regions that remain not connected yet to the internet connection network. The MCAP service program is a commitment of the Indonesian government to overcome the digital gap and equality in accessing the information and communication technology. In the Kulon Progo Regency of the Special Region of Yogyakarta (DIY), there are still areas that remain not connected yet to the internet connection network. This study aims to determine user perceptions of Mobile Community Access Point (MCAP) services in Kulon Progo based on the Technology Acceptance Model (TAM). This research used a qualitative descriptive approach with interview, observation, and documentation data collection techniques. The results show that the user perception of the MCAP service is quite good. Users are easy to use MCAP services, MCAP services are useful for increasing the performance and productivity of users in using technology, users can receive MCAP services, users have the desire to come back in using technology-based public services, users hope that MCAP service visits more often. Based on the results of the study it shows that user perception plays an important role in the development of MCAP services. With this research the MCAP manager or service provider can make improvements in terms of human resources, hardware, software, data resources, and networks.